Progress in medicinal chemistry : vol. 15. - Ellis, G. P.; West, G. B. (Amsterdam : New York : Elsevier, 1978)
In early nineteenth-century England, a spirited young woman copes with the suit of a snobbish gentleman as well as the romantic entanglements of her four sisters.
Includes bibliographical references and index.
Keywords: Phermaceutical chemistry